Tertiary lymphoid structures in gliomas: impact on tumour immunity and progression - Jiatong Chen; Yuechao Yang; Shuang Luan; Wenhao Xu; Yang Gao (Journal of Translational Medicine)
Abstract Tertiary lymphoid structures (TLSs) are ectopic lymphoid formations that develop in chronically inflamed tissues, including various solid tumours. In the context of gliomas, the presence of TLSs has recently attracted considerable attention because of their potential implications in tumour immunology and therapy. The tumour immune microenvironment (TIME) plays a crucial role in cancer progression, and tumour-infiltrating immune cells (TILs) are key players in this environment. These immune cell aggregates, known as TLSs, display distinct characteristics across different solid tumours. However, central nervous system (CNS) tumours are highly heterogeneous, and the immune environment within these tumours is often more deficient than that of peripheral tissue tumours. This leads to differences in the formation and function of TLSs in CNS tumours. These variations are particularly relevant in the context of glioma immunotherapy and could have important implications for treatment strategies. This review focuses on the composition and function of TLSs, examines the complexity of the glioblastoma (GBM) immune microenvironment, and highlights the unique characteristics of TLSs in GBM, providing new theoretical insights and practical foundations for targeting TLSs in glioma immunotherapy.